DIGITAL MEDIA HABITS ACROSS GENERATIONS: A STUDY OF MEDIA - Farida Hanim; Sofiari Ananda; Moulita; Fatma Wardy Lubis (SOSIOEDUKASI, 2025)
This study examines the media consumption habits of residents in Medan City, Indonesia, in response to the widespread adoption of smartphones and internet access. The research applies a quantitative descriptive approach using a survey of 400 respondents across generational categories (Baby Boomers, Gen X, Millennials, Gen Z, Alpha). Results reveal a dominant reliance on smartphones for accessing media content, with a declining trend in traditional television and radio use. Social media, particularly YouTube, WhatsApp, and Instagram, have become a primary source of information and entertainment, especially among young generations. The study employs uses and gratifications theory and media dependency to analyze generational differences in digital behavior. Findings indicate a significant generational shift toward mobile-centric and socially interactive media patterns, contributing to the understanding of digital audience behavior in an emerging urban context.